Mechanochemical synthesis of chemically stable isoreticular covalent organic frameworks - Biswal, Bishnu P.; Chandra, Suman; Kandambeth, Sharath; Lukose, Binit; Heine, Thomas; Banerjeet, Rahul (Journal of the American Chemical Society, 2013)
Three thermally and chemically stable isoreticular covalent organic frameworks (COFs) were synthesized via room-temperature solvent-free mechanochemical grinding. These COFs were successfully compared with their solvothermally synthesized counterparts in all aspects. These solvent-free mechanochemically synthesized COFs have moderate crystallinity with remarkable stability in boiling water, acid (9 N HCl), and base [TpBD (MC) in 3 N NaOH and TpPa-2 (MC) in 9 N NaOH]. Exfoliation of COF layers was simultaneously observed with COF formation during mechanochemical synthesis. The structures thus obtained seemed to have a graphene-like layered morphology (exfoliated layers), unlike the parent COFs synthesized solvothermally.